Somalia-Somaliland Relations: Assessing Scenarios for Negotiations and Averting Possibility of Fresh Crises in the Horn of Africa - Adan, Hassan (Technium Social Sciences Journal, 2023)
This paper focuses on the Somalia-Somaliland unresolved politico legal issue on their relationship. The contestation between the two has been dragging for a long time as a domestic issue, but due to the growing interest of both western, (re)emerging eastern and middle eastern powers, the Somalia-Somaliland sovereignty dispute is getting a new momentum and started to involve regional geopolitics. Deep political division within Somaliland over the power and resource sharing precipitated by exclusionary politics and failure of democratization efforts as well as insecurity in Somaliland’s eastern regions has finally led to armed conflict and deadly confrontations in Lasanod in Early February 2023. Because of fragility and the sensitivity of the conflicting political agendas between Somalia including Puntland and Somaliland, it attracted the attention of the United Nations Security Council, and regional bodies. Traditionally, the Horn of Africa has always been volatile for political and security dynamics. Over the past five year, the region has been shaken by the Gulf crises, followed by the US-Chinese competition over the Bab al-Mandeb strait that connects red sea to the gulf and the Indian ocean. To avert possibility of fresh escalations that may lead to regionalizing the dispute, consolidating extremism, or importing international proxy, the paper will assess three potential scenarios as methods to pursue by both authorities and by the United Nations in search for a solution of the Somalia-Somaliland question.